Cocaine Use Disorder Is Associated With Changes in Th1/Th2/Th17 Cytokines and Lymphocytes Subsets - Zaparte, Aline; Schuch, Jaqueline B.; Viola, Thiago W.; Baptista, Talita A. S.; Beidacki, Amanda Stephanie; do Prado, Carine H.; Sanvicente-Vieira, Breno; Bauer, Moisés E.; Grassi-Oliveira, Rodrigo (Frontiers in Immunology, 2019)
Background: Cocaine is a psychostimulant drug with high addictive proprieties. Evidence suggests that cocaine use leads to critical changes in the immune system, with significant effects on T, B and natural killer (NK) cells and influencing peripheral levels of cytokines. The presence of abstinence-related symptoms during detoxification treatment is known to influence the prognosis. Here, our aim was to investigate immune profiles in women with cocaine use disorder (CUD) according to withdrawal symptoms severity. Methods: Blood samples and clinical data were collected at onset of detoxification treatment of 50 women with CUD. The patients were stratified according to Cocaine Selective Severity Assessment (CSSA) scores in low withdrawal (L-W) and high withdrawal (H-W) categories. In addition, we also included a control group with 19 healthy women as reference to immune parameters. Peripheral blood was collected and lymphocyte subsets were phenotyped by multi-color flow cytometry (B cells, CD4+ T, CD8+ T, NK cells, and different stages of T-cell differentiation). PBMCs from patients and healthy controls were stimulated in vitro with phytohemagglutinin (1%) for 72 h to assess the production of Th1/Th2/Th17 cytokines. Results: Following stimulation, lymphocytes from women with CUD produced increased levels of Th1/Th2/Th17 cytokines. However, higher levels of IL-2 and IL-17 were observed only in the L-W group, while higher levels of IL-6 were detected in the H-W group compared to controls. H-W group showed lower percentage of early-differentiated Th cells (CD4+CD27+CD28+), elevated percentage of Th cells (CD3+CD4+), intermediate-differentiated Th cells (CD4+CD27-CD28+) and B cells (CD3-CD19+). Both CUD groups showed decreased percentages of naïve T cells (CD3+CD4+CD45RA+ and CD3+CD8+CD45RA+). Conclusion: Our data demonstrated that CUD can lead to increased production of Th1/Th2/Th17 cytokines and lymphocyte changes.